O vzrokih požarov v naravnem okolju - Leban, Vasja (Gozdarski vestnik, 2022)
A natural phenomenon such as a lightning strike is rarely the actual cause of a wildfire. The vast majority of fires are caused by humans - intentionally or unintentionally. Unintentionally caused fires can be classified into a group of random events that can never be avoided. More interesting for investigation and finding solutions are arsons - fires caused intentionally. The experience of fire is relatively rare and represents a stressful and traumatic event for the individual. By considering psychological findings and promoting research in the area of intentional arson, more effective measures could be found to prevent such causes of wildfire. The paper presents an aspect of wildfires that is less frequently discussed, although official statistics on the subject clearly indicates the need for improving the current situation.
Keywords: etiologija; gozdni požari; požigi; psihologija